2005
DOI: 10.1007/s00418-005-0760-y
|View full text |Cite
|
Sign up to set email alerts
|

The effect of hypophysectomy on pancreatic islet hormone and insulin-like growth factor I content and mRNA expression in rat

Abstract: The growth arrest after hypophysectomy in rats is mainly due to growth hormone (GH) deficiency because replacement of GH or insulin-like growth factor (IGF) I, the mediator of GH action, leads to resumption of growth despite the lack of other pituitary hormones. Hypophysectomized (hypox) rats have, therefore, often been used to study metabolic consequences of GH deficiency and its effects on tissues concerned with growth. The present study was undertaken to assess the effects of hypophysectomy on the serum and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…IGF-1R and key IGF-1 signaling components are present and functional in islets. [116][117][118] This somewhat supports direct effect of GH (independent of IGF-1) on beta-cell proliferation 71 (see Section 2.2 earlier). 115 However, several studies have shown that IGF-1 appears to be specifically localized to alpha cells in the islets.…”
Section: Igf-1 Signaling In Beta Cellssupporting
confidence: 66%
“…IGF-1R and key IGF-1 signaling components are present and functional in islets. [116][117][118] This somewhat supports direct effect of GH (independent of IGF-1) on beta-cell proliferation 71 (see Section 2.2 earlier). 115 However, several studies have shown that IGF-1 appears to be specifically localized to alpha cells in the islets.…”
Section: Igf-1 Signaling In Beta Cellssupporting
confidence: 66%
“…Plasma was removed and stored at À20 C. Plasma IGF-I levels were determined in undiluted samples by RIA after SepPak C18 chromatography (Waters Corp., Milford, MA, USA), as described earlier for mammals [57]. In brief, 0.15 ml PBS containing 0.2% human serum albumin (HSA), pH 7.4, was added to 0.1 ml plasma.…”
Section: Blood Sampling and Radioimmunoassay (Ria)mentioning
confidence: 99%
“…Subsequently, the antibody against CD30 was applied overnight at 4°C and visualised with Texas-red-conjugated goat anti-mouse IgG. Specificity of the antisera was tested by omitting the primary antisera as a negative control and by using sections of human breast cancer, intestine and lymph node and rat pancreas as positive controls as previously described (Eppler et al 2002;Jevdjovic et al 2004Jevdjovic et al , 2005Oberlin et al 2009;Link et al 2013) and an embryonic tumour known to contain CD30-immunoreactive cells.…”
Section: Double-immunofluorescencementioning
confidence: 99%